PENGELOLAAN PELAYANAN INFORMASI PUBLIK OLEH PEJABAT PENGELOLA INFORMASI DAN DOKUMENTASI (PPID) KABUPATEN INDRAGIRI HULU - Arsyika, Zhilli; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Indragiri Hulu regency government in 2011 has established the Information and Documentation Management Officer (PPID) which is part of the Open Government Indonesia (OGI), which Indragiri Hulu is a pilot project for the district level throughout Indonesia. PPID Indragiri Hulu to innovate in providing information services, namely the establishment of Community Information Service Center (PPIM) as part of Front desk service PPID, which is the first and only one in Indonesia. This study aimed to analyze the Management of Public Information Services by Information and Documentation Management Officer (PPID) Indragiri Hulu and to analyze the factors that influence it.Research conducted using qualitative methods to the type of exploratory research. This study uses the theory of New Public Service (NPS) proposed by Denhardt & Denhardt, consists of Serve citizens, not customers, Seek the public interest, Value citizenship over enterpreneurship, Think strategically, act democratically, Recognize that accountability isn’t simple, Serve rather than steer, and Value people, not just productivity. In this study the technique performed is observation, interview and documentation using triangulation analysis techniques.The results of this study indicate that the Management of Public Information Services by Information and Documentation Management Officer (PPID) Indragiri Hulu has been good. In addition, the Government's commitment, support from the community, as well as good communication makes the management of public information services by the Information and Documentation Management Officer (PPID) Indragiri Hulu succeed.Keywords: Services, Information, Public